2017
DOI: 10.1016/j.palaeo.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent euxinia in the high-latitude James Ross Basin during the latest Cretaceous and earliest Paleocene

Abstract: Available online xxxx Seymour Island, in the James Ross Basin, Antarctica, contains a continuous succession of latest Cretaceous sediments deposited in a shallow marine environment at high latitude, making it an ideal place to study environmental changes prior to the K-Pg mass extinction. We measured major and trace elements and conducted petrographic analysis of two sections from the Maastrichtian-Danian López de Bertodano Formation of Seymour Island. Several lines of evidence point to intermittently anoxic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…; Schoepfer et al . ) may have led to the preferential survival, and dominance of infaunal organisms following the extinction horizon in this location. Clapham () found that more motile organisms preferentially survived Mesozoic extinctions, suggesting that greater activity and therefore potentially higher respiratory physiology, controlled survival during extinction periods (Clapham ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…; Schoepfer et al . ) may have led to the preferential survival, and dominance of infaunal organisms following the extinction horizon in this location. Clapham () found that more motile organisms preferentially survived Mesozoic extinctions, suggesting that greater activity and therefore potentially higher respiratory physiology, controlled survival during extinction periods (Clapham ).…”
Section: Discussionmentioning
confidence: 93%
“…; Schoepfer et al . ). These indicate that the LBF represents a series of palaeoenvironments, ranging from estuarine to shallow marine (mid‐shelf) (Macellari ; Olivero et al .…”
Section: Geological Settingmentioning
confidence: 97%
“…In the case of bioeroded fossil bones, a change in chemical conditions must have occurred during the early burial history of the bone (Trueman and Martill 2002). Intermittent euxinia appears to have been a characteristic feature of this high-latitude environment during the Cretaceous-Paleogene in López de Bertodano Formation (Schoepfer et al 2017). These chemical fluctuations could have inhibited bioerosion and this contributed to the preservation of the histological structures in the analyzed sample.…”
Section: Discussionmentioning
confidence: 99%
“…These beds represent transgressive shelf deposits followed by a regressive trend in the uppermost part of the López de Bertodano Formation (Olivero 2012). According to Schoepfer et al (2017), several lines of evidence point to intermittently anoxic to euxinic conditions during deposition, including the presence of pyrite framboids with a size distribution suggesting syngenetic formation in the water column.…”
Section: Geological Settingmentioning
confidence: 99%
“…Reduction of organic matter under reducing conditions leads to the formation and preservation of iron pyrite, making S-Fe-TOC relationships particularly informative of paleo-redox conditions and early stage sedimentary diagenesis. A number of trace elements that typically occur in enhanced concentration in organic-rich shales are commonly hosted by pyrite, or other sulphide mineral phases, as well as organic matter (Schoepfer et al, 2017). On this basis, paleo-redox conditions can be assessed by the proportion of S relative to Fe (Raiswell et al, 1988;Lyons & Severmann, 2006;Georgiev et al, 2012).…”
Section: Sulphur -Iron -Carbon Relationshipsmentioning
confidence: 99%